ความรู้ความเข้าใจเกี่ยวกับประชาธิปไตยของนักเรียนชั้นมัธยมปีที่สาม ในจังหวัดอุบลราชธานี - สถิต จิตตะนาคี (จุฬาลงกรณ์มหาวิทยาลัย, 1975)
Purpose The purpose of this study was to compare the understanding of democracy among Mathayom Suksa Three Students, male and female. Procedures The test on democracy which had a reliability at 0.71 constructed by the writer was administered to 400 students who were randomly sampled from the secondary schools in Ubon Rajadhanee Province. Then, the test results were treated by the statistical methods of z – test and chi – square for the item analysis. Conclusions and Recommendations It was found that the z – test for the understanding of democracy of both male and female students was not significantly different at the .05 level of confidence. Besides, the chi – square of the item analysis revealed that only 17 test items were dependent upon the sexes of the students to answer right or wrong. The other 47 test items were not. It could be said that, to develop the understanding of democracy among the students, home, the school, and the community should cooperate seriously in both the environment arrangement and the practice of their knowledge. The school should adjust the methods of teaching in accordance with the democratic principles. Some modern teaching techniques, such as the inquiry method, should be utilized to fulfill the need to increase their knowledge, skill, and humanistic values in order to be able to make decision by using reliable information on which is relevant to democratic principles and beliefs.